ANALISIS PENGEMBANGAN PERIKANAN BUDIDAYA SISTEM KJA DI DUSUN WAEL KABUPATEN SERAM BAGIAN BARAT - Karepesina, Musa; Sangadji, Nur Fatimah; Saimima, Nur Asyah; Arif, Desilina; Payung, Damaris (Universitas Pattimura, 2024)
Research analysis of aquaculture development with KJA system in Wael sub village, West Seram Regency aims to analyze the internal and external environmental factors of development and formulate strategies and development priorities. The research was located in Wael sub village, West Seram Regency, with consideration of the locus selection because there are several KJA system fish farming businesses, and was conducted from October to December 2023. Aquaculture development analysis data were obtained through SWOT analysis, while the priority strategy for aquaculture development in Wael sub village was determined through AHP analysis. Identification of the internal environment and external environment formulated in an effort to analyze the development strategy of aquaculture business with KJA system in the waters of Wael sub village inventoried 5 components of strength, 5 components of weakness, 5 components of opportunities and 4 components of threats related to the development of aquaculture business using KJA system in Wael sub village, West Seram Regency. The results of the analysis of the priority of aquaculture business development strategies with the KJA system in the waters of Wael sub village resulted in the prioritization of five development strategies that have been produced in the TOWS analysis, namely: a) optimizing the development of aquaculture with KJA system in the waters of Wael sub village; b) Equalizing the quality of human resources and infrastructure of aquaculture with KJA system in the waters of Wael sub village; c) Expansion of cooperation networks in the development of aquaculture with KJA system in the waters of Wael sub village; d) Preservation of the quality of waters of Wael sub village; e) Increased ability to access capital for aquaculture with KJA system in the waters of Wael sub village, West Seram Regency.